Health-Related Quality of Life of People with Physical Disability in South-South, Nigeria - N. E., Andrew-Essien; N., Ojule I. (International Journal of Innovative Research in Medical Science, 2020)
Background: The global increase in non-communicable diseases and increased aging of most populations is projected to have a profound effect on the overall prevalence of disability. Quality of life is a concept that has become fundamental to assessing life and living of all individuals more so for people with disabilities. In this study, we focused on assessing the quality of life of persons with mobility disabilities in Rivers State, Nigeria, identifying factors that influence their quality of life from their perspective. Materials and Methods: A descriptive, cross-sectional design was used in conducting this study among 179 subjects with a physical disability, specifically mobility impairment. The inclusion criterion was all persons with a physical disability. Exclusion criteria were children (0-17 years) with any form of disability, persons with intellectual, visual and hearing impairments. We used a Two-Stage sampling process using a computerized random number generator. The study tool was the (7) WHOQOL - BREF questionnaire which was both self and interviewer-administered. Data were analyzed using both descriptive and inferential statistics. Significance was set at P≤0.05. Results: The lowest and the highest mean scores of WHOQOL-BREF domains were found for the social relationships domain (Mean = 10.58) and the environmental health domain (Mean = 23.52), respectively. The mean age of respondents was 38.49 ± 10.89years. Respondents ≤34 years of age had a higher mean overall QoL scores (2.71 ± 1.04) than those above 34 years (2.57 ± 1.10). A significance was observed between age and physical health. Education years was significantly associated with two domains (psychological and environment), Employment status was associated with two domains (psychological and social relationships), and the onset of disability associated with the psychological domain (p<0.05). Conclusion: Quality of life was relatively low across the four health-related domains, with the social relationship domain recording the lowest mean QoL scores. The factors that had significant positive relationships with various domains of quality of life were level of education, gender, age, occupation and activities of daily living. In Nigeria, disability status is still largely absent from routine data collection. This study adds to bridging the gap in evidence-based research on disability.